MASLAHAT DALAM KONSEP MAQASHID AS-‎SYA’RIAH ANTARA PEMIKIRAN AL-GHAZALI, AL ‎SYATHIBI, DAN IBNU ASHUR - Muttaqin Muttaqin; Muhammad Farid (IAIN Ambon, 2023)
The study of religious knowledge is a very important thing, especially in ‎today's era, including with this Sya'riah maqashhid. Where through the maqashid ‎sya'riah, these verses and hadiths regarding law are still quantitative and very limited, ‎the number can be developed to deal with problems that are not directly ‎accommodated in the verses of the Qur'an and also the hadiths. -hadith. So in this ‎study, we will describe the maqashid sya'riah thinking between Imam Al-Ghazali, ‎Imam Syattibi, and also Ibn Ashur. Maqashhid Sya'riah is the first step that must be ‎passed as a Muslim in order to be able to implement the fact that religion and its ‎teachings are always relevant forever. So that it can provide a solution for every ‎problem that will arise at some point in the future.‎